Differences of Quercetin Content in Fresh and Extracts Local Apples using High Performance Liquid Chromatography Method - Nila Authoria; Lilik Wijayanti; Ratih Puspita Febrinasari (Research Synergy Foundation, 2022)
Background : Oxidative stress is an imbalance between pro-oxidants and endogenous antioxidants resulting in cell damage and degenerative diseases. As horticultural commodities, apples have superior varieties of Manalagi and Romebeauty. Apples contain exogenous antioxidants, namely quercetin that effectively contributes to the management of oxidative stress. Purpose : The study used laboratory experimental methods to determine differences in quercetin content in fresh apples and apple extracts of Manalagi and Romebeauty. Research methodology : Determination of quercetin content of fresh apples and apple extract used the High Performance Liquid Chromatograph (HPLC) method. The samples used were fresh apples and apple viscous extract of Manalagi and Romebeauty obtained respectively from UPT Medika Material Laboratory of Batu City and Food Engineering Laboratory of Soegijapranata Catholic University Semarang using maceration process with ethanol solvent.Findings : The results showed that the average levels of quercetin in fresh apples of Manalagi and Romebeauty varieties were 13,685 ppm and 15,544 ppm respectively. Extraction of 70% ethanol from 100 grams of Manalagi and Romebeaty varieties resulted in 38.123 grams and 52.699 grams of thick extract. The average levels of quercetin in Manalagi and Romebeauty extracts were 422.235 ppm and 243.454 ppm. It can be concluded that the extract can optimize the quercetin content. Research limitations : The quercetin content in local apple extracts of Manalagi and Romebeauty can be used as an alternative to antioxidant therapy due to oxidative stress. Originality/value : Analyzing differences in quercetin content in fresh apples and apple extracts.